SEJARAH DAN PERAN PESANTREN DALAM PENDIDIKAN DI INDONESIA - Adnan Mahdi (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
Pesantren is the oldest and unique educational institution which has Indonesian characteristics, therefore, many studies have been conducted from different perspectives, especially in the terms of periodisation of its history. However, the study appears to be so broad and described in general while correlating with the role and its progress involved. On this basis, this paper will examine deeper in the role of pesantren in the context of history of education in Indonesia. Based on the historical analysis through library research, the study shows that pesantren in Indonesia is periodically divided into five periods, viz: emergence, development, evolution, ideological fortress, and Muslims media development. While the role of pesantren is to be the source in formulating the national education system, preparing the educational and intellectual figures and the character education model.